Induced pluripotent stem cells for modeling of pediatric neurological disorders. Issue 7 (25th June 2014) - Jang, Jiho; Quan, Zhejiu; Yum, Yunjin J.; Song, Hyo Sook; Paek, Seonyeol; Kang, Hoon‐Chul
Abstract The pathophysiological mechanisms underlying childhood neurological disorders have remained obscure due to a lack of suitable disease models reflecting human pathogenesis. Using induced pluripotent stem cell (iPSC) technology, various neurological disorders can now be extensively modeled. Specifically, iPSC technology has aided the study and treatment of early‐onset pediatric neurodegenerative diseases such as Rett syndrome, Down syndrome, Angelman syndrome. Prader–Willi syndrome, Friedreich's ataxia, spinal muscular atrophy (SMA), fragile X syndrome, X‐linked adrenoleukodystrophy (ALD), and SCN1A gene‐related epilepsies. In this paper, we provide an overview of various gene delivery systems for generating iPSCs, the current state of modeling early‐onset neurological disorders and the ultimate application of these in vitro models in cell therapy through the correction of disease‐specific mutations.